Banzhilian formula alleviates psoriasis-like lesions via the LCN2/MMP-9 axis based on transcriptome analysis - Xing, Meng; Yan, Xiaoning; Guo, Jiangtao; Li, Wenbin; Li, ZhangJun; Dong, Chun; Guo, Jiao; Qu, Keshen; Luo, Ying (Frontiers in Pharmacology, 2023)
Oral Banzhilian Formula (BZLF) is effective in the clinical treatment of psoriasis. However, the effectiveness and mechanism of different drug delivery routes deserve further study. In this study, we externally applied BZLF to the skin lesions in an IMQ-induced psoriasis mice model, and found that BZLF alleviated the psoriasis-like skin lesions, while inhibiting the expression of Ki67 and inflammatory factors (Il17a, Tnf-α, S100a7 and Cxcl1) in the skin lesions. Finally, through transcriptome sequencing combined with bioinformatics and other methods, it was found that the mechanism of action of BZLF against psoriasis is achieved by down-regulating the LCN2/MMP-9 axis. Overall, this study elucidates the effectiveness and mechanism of external application of BZLF in the treatment of psoriasis, and provided a new approach and basis for clinical application.